Markets, Contracts, and Uncertainty in a Groundwater Economy - Gine, Xavier; Jacoby, Hanan G. (World Bank, Washington, DC, 2016)
Groundwater is a vital yet threatened resource in much of South Asia. This paper develops a model of groundwater transactions under payoff uncertainty arising from unpredictable fluctuations in groundwater availability during the agricultural dry season. The model highlights the trade-off between the ex post inefficiency of long-term contracts and the ex ante inefficiency of spot contracts. The structural parameters are estimated using detailed micro-data on the area irrigated under each contract type combined with subjective probability distributions of borewell discharge elicited from a large sample of well-owners in southern India. The findings show that, while the contracting distortion leads to an average welfare loss of less than 2 percent and accounts for less than 50 percent of all transactions costs in groundwater markets, it has a sizeable impact on irrigated area, especially for small farmers. Uncertainty coupled with land fragmentation also attenuates the benefits of the water-saving technologies now being heavily promoted in India.